(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
This study purpose to analyze the characteristics of the research carried out on models of insolvency prediction in the Brazilian context, based on a fragment of the literature. To this end, a Bibliographic Portfolio was created based on a search in the SPELL database - Scientific Periodicals Electronic Library, using the term insolvency forecasting models, resulting in 18 articles for the analysis of basic and advanced variables. The research results show that the most used insolvency forecasting models are Elisabetsky (1976); Matias (1976); Kanitz (1978); Altman, Baidya and Dias (1979); Silva (1982); and, Sanvicente and Minardi (1998). It is concluded that although the research theme is not new, there is stillroom for expansion, having to be observed the previous studies and their evolution for the development and application of the models. The findings are expected to contribute to researchers in the field and make it possible to encourage the application of insolvency forecasting models in companies.